FEDERAL GOVERNMENT DOMESTIC CHARACTERISTICS AND ECONOMIC REVITALIZATION IN NIGERIA (1990 – 2023) (Journal of Contemporary Issues in Accounting, 2024)
This study investigated the complex relationship between the domestic characteristics of federal government and the economic revitalization of Nigeria from 1990 to 2023, with a specific focus on key economic variables: Gross Domestic Product (GDP), treasury bonds, and treasury bills. Over these three decades, Nigeria has experienced significant political, social, and economic transformations, driven by various government policies, institutional reforms, and socio-political dynamics. Key areas of investigation include Economic Growth which was measured with GDP (dependent variable) and the treasury bonds and treasury bills which both served as measures for domestic characteristics (the independent variable).. The study assesses how these instruments have been used to stimulate economic growth. Thus, it employed a mixed-methods approach, combining quantitative data analysis of economic indicators with qualitative insights from policy documents and case studies. The quantitative analysis includes evaluating GDP growth, treasury bond and treasury bill yields. Qualitative insights are derived from analyzing policy documents, and case studies to provide a comprehensive understanding of the federal government's role in economic revitalization. Findings made indicated that there is positive but no significant relationship between Treasury bonds and economic growth in Nigeria during the period 1990-2023. It was also established that there is co-integration between gross domestic product growth rate and Treasury bills in Nigeria. Also, while certain federal initiatives have spurred economic development, challenges such as bureaucratic inefficiency, policy inconsistency, and regional disparities have hindered sustained progress. The study concludes with policy recommendations aimed at enhancing the federal government's role in fostering a more resilient and inclusive economic environment in Nigeria. These recommendations include monitoring the disbursement of loans on real growth enhancing capital projects instead of recurrent expenditure. Also, there is evident need to strengthen governance frameworks, improve on fiscal policy management with a focus on effective use of treasury instruments, deepen institutional reforms, addressing regional disparities, and fostering greater socio-political engagement to ensure sustainable economic growth and development.
Keywords: Domestic characteristics; Economic revitalization; Gross Domestic Product; Treasury Bond; Treasury bills